EFEKTIVITAS KUIS ONLINE KAHOOT!DALAMMENINGKATKAN KEMAMPUAN KOGNITIF SISWAPADA PEMBELAJARAN FISIKA MATERI GERAK MELINGKARDIKELAS X SMA NEGERI 8 PEKANBARU - Winnie Yulis Peranti; Fakhruddin Fakhruddin; Zulirfan Zulirfan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract:This study aims to describe the cognitive abilities of students and determine differences in cognitive abilities ofstudentsgrade Xof SMA Negeri 8 Pekanbaru by using theKahoot!online quizin physics learningand conventional learning on circular motion material.The type of research used is quasi-experimentaland research design is intact group comparison. The research subjects were class X students of SMA 8PekanbaruAcademic Year 2019/2020which amounted to 72 students. Research data is learning outcome data consisting of post-test scores through after the use of the Kahoot!online quiz. Data were analyzed descriptively and inferentially to see how students' cognitive abilities improve after using the Kahoot!online quiz.The results of the analysis of the data obtained were, the absorption rate of the experimental class was higher than the absorption rate of the control class with the absorption score of the experimental class average of 81,48and the absorption rate of the control class average 70,93. The effectiveness of learning refers to the average absorptive score of each class with an experimental class score of 81.48belong tothe effective category and the control class 70.93belong tothe effective category. Based on the hypothesis test carried out obtained a significance value (sig.2-tailed) 0.000 <0.05 so it can be concluded that there are significant differences between students' cognitive abilities after using the Kahoot!online quizand conventional learning.KeyWords:Kahoot!Online Quiz, Cognitive Abilities, Circular Motion.